2023
DOI: 10.1093/cvr/cvad007
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein QKI governs a muscle-specific alternative splicing program that shapes the contractile function of cardiomyocytes

Abstract: Aims In the heart, splicing factors orchestrate the functional properties of cardiomyocytes by regulating the alternative splicing of multiple genes. Work in embryonic stem cells has shown that the splicing factor Quaking (QKI) regulates alternative splicing during cardiomyocyte differentiation. However, the relevance and function of QKI in adult cardiomyocytes remains unknown. In this study we aim to identify the in vivo function of QKI in the adult mouse heart. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…It is also worth mentioning that many other RBPs, which are not discussed in this review, are involved in regulating the alternative splicing of cardiac genes, although no cardiomyopathy phenotypes were firmly associated with loss of their function. For example, the cardiomyocyte-specific deletion of Mbnl1 and Mbnl2 in mice causes heart spliceopathy [ 101 ], and the conditional knockout of QKI in the cardiomyocytes of adult mice leads to heart failure by disrupting the alternative splicing of cardiac genes with functions in the sarcomere and cytoskeleton [ 102 ]. Thus, we may expect that their combined actions coordinate alternative splicing events in heart development, function, and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning that many other RBPs, which are not discussed in this review, are involved in regulating the alternative splicing of cardiac genes, although no cardiomyopathy phenotypes were firmly associated with loss of their function. For example, the cardiomyocyte-specific deletion of Mbnl1 and Mbnl2 in mice causes heart spliceopathy [ 101 ], and the conditional knockout of QKI in the cardiomyocytes of adult mice leads to heart failure by disrupting the alternative splicing of cardiac genes with functions in the sarcomere and cytoskeleton [ 102 ]. Thus, we may expect that their combined actions coordinate alternative splicing events in heart development, function, and homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous changes in alternative splicing were identified, mostly in sarcomeric, cytoskeletal and Ca 2+ -handling genes. We thus concluded that QKI is a major regulator of striated muscle identity by governing a muscle-specific alternative splicing program in cardiomyocytes ( Montañés-Agudo et al, 2023a ). This extended earlier studies, in which an essential role for QKI was demonstrated in cardiomyocyte differentiation of cardiac progenitors and in the specification of cardiac mesoderm ( Chen et al, 2021 ; Fagg et al, 2022 ).…”
Section: Introductionmentioning
confidence: 92%
“…Our laboratory has recently generated a mouse model with a conditional deletion of Qki in cardiomyocytes to study the function of QKI in the heart ( Montañés-Agudo et al, 2023a ). Removal of Qki in the adult heart induces dilation of the ventricles and a rapid decline in cardiac function, and this is associated with severe disruption of sarcomere organization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A spliceosome is composed of five small nuclear ribonucleoproteins (snRNPs) and over 100 auxiliary proteins and have been extensively studied and reviewed. 7 , 8 , 9 Non-snRNP factors involved in splicing or AS include serine and arginine-rich (SR) proteins 10 ; heterogeneous nuclear ribonucleoproteins (hnRNPs) 11 ; hnRNP-like proteins (such as RBFOX proteins, 12 CELF proteins, 13 NOVA, 14 TDP-43 15 and QKI 16 ); and other regulators, such as MBNL, 17 HuR 18 and RBM proteins. 19 , 20 Among them, SR proteins and hnRNPs are the most important splicing factors that regulate AS, inhibiting strong splice sites or amplifying the power of weak splice sites.…”
Section: Splicing Factors and Cardiovascular Diseasementioning
confidence: 99%